Hydrologic connectivity amplifies riverine N 2 O emission hot spots and hot moments across the contiguous United States - Minpeng Hu; Zhongjie Yu; Timothy J. Griffis; Kelly Aho; Yucang Wang; Jie Yang; Wendy H. Yang; Carl J. Bernacchi; Justin M. McGrath; Randy A. Dahlgren; Hanqin Tian; John M. Baker (Proceedings of the National Academy of Sciences, 2026)
Riverine nitrous oxide (N 2 O) emissions constitute a significant yet uncertain component of global greenhouse gas budgets. Integrating approximately 3,600 observations across the contiguous United States (CONUS), we present a monthly resolved, national-scale estimate of riverine N 2 O emissions (60.7 Gg N 2 O-N y −1 ; 95% CI: 41.9 to 71.2) using a machine-learning framework. Our analysis reveals that enhanced hydrologic connectivity strongly regulates nitrogen and N 2 O delivery to streams, driving emission hot moments during high-flow periods, especially in nutrient-rich low-order streams. The Midwest Corn Belt is identified as a major emission hot spot, where seasonal increases in connectivity (e.g., late-winter thaws and postharvest rainfall) amplify riverine emissions relative to direct soil emissions. Our watershed-specific EF 5r (0.0005 to 0.029) exceeds the IPCC default (0.0026) by more than twofold on average and up to 10-fold in intensively managed watersheds. These findings highlight the importance of incorporating hydrologic connectivity and nitrogen transport into climate models and watershed nitrogen management strategies.